1998
DOI: 10.1002/(sici)1097-0339(199804)18:4<291::aid-dc9>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic papillary oncocytic carcinoma of the pancreas to the liver diagnosed by fine-needle aspiration

Abstract: A 37‐year‐old white male with a large pancreatic mass was referred to our institution with a hypodense liver lesion detected on CT scan. A fine‐needle aspiration (FNA) was performed on the liver lesion. Diff‐Quik smears demonstrated scattered papillary structures and single neoplastic cells with abundant well‐defined dense granular cytoplasm. Eccentrically located nuclei were noted with single prominent nucleoli. Cell block preparations showed papillary structures lined by cells with abundant pink granular cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 18 publications
(28 reference statements)
2
13
0
Order By: Relevance
“…Although the cytologic features of IPMNs are well established, the cytologic features of IOPNs (oncocytic‐type IPMNs) are described only rarely and mainly in isolated reports . This is probably related in part to the rarity of the entity, but it is also somewhat attributable to a lack of recognition, which we hope the current study will alleviate to some degree.…”
Section: Discussionmentioning
confidence: 99%
“…Although the cytologic features of IPMNs are well established, the cytologic features of IOPNs (oncocytic‐type IPMNs) are described only rarely and mainly in isolated reports . This is probably related in part to the rarity of the entity, but it is also somewhat attributable to a lack of recognition, which we hope the current study will alleviate to some degree.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Since the IOPN entity was first described by Adsay et al in 1996, only 31 cases have been reported. 3,[7][8][9][10][11][12][13][14][15][16][17][18][19][20] The average age of patients was 63.0 years (range, 37-79 years), and the male : female ratio was 1.1:1. Most IOPN were located in the pancreatic head (60.0%), and the average tumor size was 6.40 cm (range, 1.69-15.0 cm).…”
Section: Discussionmentioning
confidence: 99%
“…Of the total 14 patients reported in the literature, recurrence was noted in 1, metastases developed in 1, 3 died postoperatively, 1 died of other causes, and 8 were alive with no evidence of disease (Table 1). [9][10][11] However, there are insufficient data in the literature to determine the clinical course of intraductal oncocytic papillary neoplasm, although the biological behavior of this tumor seems to be better than that of ductal carcinoma. We recently described the clinicodiagnostic features of malignant and benign intraductal papillary tumors of the pancreas to assist us in the selection of appropriate treatment.…”
Section: Discussionmentioning
confidence: 99%